Beyond Prohibition: A Proposal for an International Treaty on Parental Readiness to Safeguard Child Welfare - Maximillian Kenas Tarmidi (Fakultas Hukum Universitas Airlangga, 2026)
Globalization has accelerated the erosion of traditional social structures, creating a vacuum where the welfare of children is increasingly precarious. This new landscape presents dual threats: the normalization of